Nights of the Magician: Borges, Dreams, Cortázar, Writing and Gnosticism - Jaeck, Lois Marie (CIENCIA ergo-sum; Vol. 5 Núm. 1 (1998): CIENCIA ergo-sum (marzo-junio 1998), 2017)
Jorge Luis Borges' short story Las ruinas circulares establishes a parallel between dream, the creative process and gnosticism. While Borges never forges any direct link between his character's dream "son" and his own short story, he establishes the connection between dreams and writing in several critical writings. Julio Cortázar —frequently- described as Borges' the "hijo espiritual' reflects in his own writing the connection between dream and writing expounded by Borges. For example, Cortázar's short story Continuidad de los parques mirrors the lack of distinction between dream and reality that is implicit in Borges' Las ruinas circulares. Just as Borges' magician reflects the possible "dream" reality of humankind in general (a creation in the mind of a god who may be the self-referential reflection of humanity), so Cortázar's man in the green armchair reflects humanity in 'flesh and blood", enmeshed in the sign systems of language to such an extent that it is only a linguistic function in a play of repetition and difference that for all practical purposes renders the distinction between "appearance" and "reality" quite insignificant.